Innovation of Pragmatic Approach through Test in Maharah Istima’ in Arabic Language Book Class V Kemenag 2020 - Hanna Sajida Fitria; R. Umi Baroroh; Nurul Kamaliah; Faizah Kamila (Universitas Muhammadiyah Mataram, 2025)
Abstract: Arabic language learning at the Madrasah Ibtidaiyah level still demonstrates weaknesses in contextual assessment of maḥārah istimā’ (listening skills). The evaluation in the Grade V Arabic Textbook published by the Ministry of Religious Affairs in 2020 remains traditional and has not yet comprehensively assessed students’ ability to understand meaning contextually. Based on this condition, this study aims to develop an innovative pragmatic approach in the assessment of maḥārah istimā’. This approach integrates pragmatic principles into test formats that evaluate students’ comprehension of contextual meaning rather than focusing solely on linguistic aspects. The subjects of this study are Madrasah Ibtidaiyah students who use the textbook in their learning process. The study employs a descriptive qualitative method, focusing on the analysis of assessment forms relevant to real communicative contexts. The findings indicate that applying a pragmatic approach in assessing maḥārah istimā’ provides a more authentic evaluation of students’ listening ability. This approach enhances the relevance, effectiveness, and functionality of Arabic language comprehension in everyday life contexts.Abstrak: Pembelajaran bahasa Arab di tingkat Madrasah Ibtidaiyah masih menunjukkan kelemahan dalam penilaian maḥārah istimā’ yang kontekstual. Evaluasi dalam Buku Bahasa Arab Kelas V terbitan Kementerian Agama tahun 2020 cenderung tradisional dan belum menilai kemampuan pemahaman makna secara menyeluruh. Berdasarkan hal tersebut, penelitian ini bertujuan untuk mengembangkan pendekatan pragmatik yang inovatif dalam penilaian maḥārah istimā’. Pendekatan ini berupa integrasi prinsip-prinsip pragmatik ke dalam bentuk tes yang menilai kemampuan pemahaman makna kontekstual siswa, bukan sekadar aspek linguistik. Subjek penelitian ini adalah siswa Madrasah Ibtidaiyah yang menggunakan buku tersebut dalam proses pembelajaran. Penelitian ini menggunakan metode deskriptif kualitatif dengan analisis terhadap bentuk penilaian yang relevan dengan konteks komunikasi nyata. Hasil penelitian menunjukkan bahwa penerapan pendekatan pragmatik dalam penilaian maḥārah istimā’ mampu menampilkan evaluasi yang lebih autentik terhadap kemampuan mendengar siswa. Pendekatan ini meningkatkan relevansi, efektivitas, serta fungsionalitas pemahaman bahasa Arab dalam konteks kehidupan sehari-hari.